DnaJ homolog Hdj2 Facilitates Japanese Encephalitis Virus Replication - Wang, Robert Yung-Liang (BioMed Central, 2011)
BACKGROUND: Japanese encephalitis virus (JEV) is a member of the mosquito-borne Flaviviridae family of viruses that causes human encephalitis. Upon infection of a new host, replication of viral RNA involves not only the viral RNA-dependent RNA polymerase (RdRp), but also host proteins. Host factors involved in JEV replication are not well characterized. RESULTS: We identified Hdj2, a heat-shock protein 40 (Hsp40)/DnaJ homolog, from a mouse brain cDNA library interacting with JEV nonstructural protein 5 (NS5) encoding viral RdRp using yeast two-hybrid system. Specific interaction of Hdj2 with NS5 was confirmed by coimmunoprecipitation and colocalization in JEV-infected cells. Overexpression of Hdj2 in JEV-infected cells led to an increase of RNA synthesis, and the virus titer was elevated approximately 4.5- to 10-fold. Knocking down of Hdj2 by siRNA reduced the virus production significantly. CONCLUSIONS: We conclude that Hdj2 directly associates with JEV NS5 and facilitates viral replication. This study is the first to demonstrate Hdj2 involved in JEV replication, providing insight into a potential therapeutic target and cell-based vaccine development of JEV infection.